(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
From the numerous legal competencies envisaged by the Law on Ombudsmen, this reserch focuses on the competence of exercising control over the legality, as well as the expediency of the undertaken actions and the decisions made by the employees in the public authorties in the Republic of Macedonia (public administration). The aim of this reserch is analysis of one segment, from the numerous competencies, and observations of the activities undertaken by the Ombudsman as an investigator of the work of the public administration in the Republic of Macedonia. The survey uses the method of analysis of the laws and sublaws, statistical indicators, as well as other relevant indicators that indicate the role of the Ombudsman in the Republic of Macedonia as an investigator of the work of the public administration. The results of the survey portray the measures the Ombudsman has undertaken in it’s role of performance in protecting human rights and freedoms when citizens are seeking services by the public administration.